Hierarchies and fractals: ecclesiastical revenues as indicator for the distribution of relative demographic and economic potential within the cities and regions of the Late Byzantine Empire in the early 14th century - PREISER-KAPELLER, Johannes; MITSIOU, Ekaterini (Byzantina Symmeikta, 2011)
Until now the source material has made it impossible to reconstruct the distribution of economic power and population within the Late Byzantine Empire on a large scale. Our new analysis of a list of financial contributions from 1324, which includes those from 33 bishoprics and the Patriarchate of Constantinople, connects this data with the economic performance of the respective town and its hinterland; we demonstrate that the distribution of contributions shows characteristics which are typical for settlement hierarchies and therefore can be used to create the first models for the relative distribution of demographic and economic potential in the Byzantine Empire at this time.